(untitled) (Progressive Agriculture, 2013)
This study was undertaken to determine and compare the profitability of Boro rice and potato production. In total 60 farmers of which 30 Boro rice growers and 30 potato growers were selected randomly from four villages of Gouripur Upazila in Mymensingh district. Descriptive as well as statistical analysis were done to achieve the objectives of the study. The Cobb-Douglas production function was used to determine the effects of individual inputs on Boro rice and potato production. The major findings of the study were that the cultivation of Boro rice and potato was profitable from the view point of farmers. The per hectare total return from Boro rice and potato were Tk. 83,320.00 and Tk. 2,62,625.22 respectively. The gross cost of Boro rice and potato production were Tk. 54,202.74 and 1,20,221.71 respectively. Again the net return from Boro rice and potato were Tk. 24,117.26 and 1,42,403.51 respectively. The Benefit Cost Ratio (BCR) was 1.41 and 2.18 respectively for Boro rice and potato production. The results indicated that potato production was more profitable than Boro rice production. It was also evident from the study that per hectare net returns were influenced by most of the factors included in model. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16880 Progress. Agric. 20(1 & 2): 253 258, 2009